Comparison of Outcomes between Laparoscopy and Laparotomy in Colorectal Cancer at Dr. Cipto Mangunkusumo Hospital - Jeo, Wifanto Saditya; Noorsukma, Hutomo Rezky (http://dharmais.co.id/, 2026)
Background: Colorectal cancer (CRC) is one of the most common types of cancer in the world and a leading cause of cancer-related deaths. Laparotomy is the standard curative treatment for localized disease. Laparoscopy offers several advantages, including less postoperative pain, shorter hospital stays, faster recovery, and lower risk of infection. Therefore, we conducted this study to evaluate the outcomes of laparoscopy versus laparotomy in CRC, particularly at Dr. Cipto Mangunkusumo Hospital, Jakarta. Methods: This retrospective study included CRC patients who underwent laparoscopy (56 subjects) and laparotomy (79 subjects) from 2022 to 2024 in Dr. Cipto Mangunkusumo Hospital. Inclusion criteria were: patients aged over 18 years, diagnosed with stage I–III colorectal cancer, and treated with either laparoscopic or open surgical resection. The outcomes were hospital stay, intraoperative blood loss, complications, surgical duration, and surgical fee. Chi-square test was used for categorical variables, and the independent T-test was used for continuous variables.Results: A total of 135 CRC patients (54.8% female) with a mean age of 54.74±12.90 years old were recruited in this study. Nearly half of the patients (49.6%) had tumors located in the rectum. We found that laparoscopy was associated with a lower risk of postoperative complications (OR = 0.091; 95%CI 0.011–0.777; p = 0.008) and a lower risk of 2-year mortality (OR = 0.395; 95% CI 0.178–0.878; p = 0.054). We found no significant difference between hospital stay, intraoperative blood loss, surgical duration, and surgical cost in bivariate analysis. Multivariate analysis revealed significant differences in surgery duration (B -0.196; p = 0.025) and surgical fee (B 0.263; p = 0.028), with no significant differences in blood loss, postoperative complications, treatment duration, and 2-year mortality rate.Conclusions: Laparoscopic surgery offers significant lower risk of postoperative complications. Although it was not statistically significant, we also found that laparoscopy had a lower trend of 2-year mortality. These findings support the use of laparoscopy as a safe approach for appropriately selected patients, though further studies are warranted in complex and advanced cases.